TECHNOLOGY OF TRAINING OF FUTURE TEACHERS WITH NONTEACHING SPECIALTIES TO TEACHING WORK - Modestova, Т.В. (Journal of Information Technologies in Education (ITE), 2014)
The ways of information and communication technologies implementation into the process of the future higher school teachers’ readiness formation for pedagogical activities, who are going to get non-pedagogical Master degree are considered in the article. ICT usage expedience at students’ individual work is proved. The proper information resources and communication ways of the educational process participants are found. Technique of informational assets usage during “Theory and Practice of Higher School” course studying is developed. It is based on author’s teaching and learning aids and Internet accessible. It has been proved that supplying educational process with the updated information and communication technologies enables students to perform an effective preparation for the classes independently; supports their skills for individual work and creativity performance; develops motivation for the pedagogical course studying and future teaching activities at higher school.